2019
DOI: 10.1002/ange.201911861
|View full text |Cite
|
Sign up to set email alerts
|

Microporosity of a Guanidinium Organodisulfonate Hydrogen‐Bonded Framework

Abstract: Guanidinium organosulfonates (GSs) are al arge and well-explored archetypal family of hydrogen-bonded organic host frameworks that have,o vert he past 25 years, been regarded as nonporous.Reported here is the only example to date of ac onventionally microporous GS host phase, namely guanidinium 1,4-benzenedisulfonate (p-G 2 BDS). p-G 2 BDS is obtained from its acetone solvate,A cMe@G 2 BDS, by single-crystal-to-single-crystal (SC-SC) desolvation, and exhibits aT ype Il ow-temperature/pressure N 2 sorption isot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In this seminal study, the bowl-shaped molecule p-tert-butylcalix [4]arene was shown to include a guest molecule in discrete cavities despite the absence of channels. Subsequently, other non-porous molecular materials exhibiting dynamic and cooperative guest transport were reported [38][39][40][41][42][43][44][45] .…”
Section: Preparation and Characterization Of 1 Dmfmentioning
confidence: 99%
“…In this seminal study, the bowl-shaped molecule p-tert-butylcalix [4]arene was shown to include a guest molecule in discrete cavities despite the absence of channels. Subsequently, other non-porous molecular materials exhibiting dynamic and cooperative guest transport were reported [38][39][40][41][42][43][44][45] .…”
Section: Preparation and Characterization Of 1 Dmfmentioning
confidence: 99%
“…KUF‐1, self‐assembled from tetra‐sulfonate anions and guanidinium cation is also thermally stable in the range of 298–573 K. It can keep high crystallinity in the range of 298–423 K. The unique S‐shape NH 3 adsorption behavior and good reusability make it a promising adsorbent for effective NH 3 capture [42] . Recent research discovered that gas pressure imposition could regenerate porous structures from collapsed nonporous GS frameworks [43] . That paves a fresh avenue for the permanent porosity establishment and functional application of GS frameworks.…”
Section: Rational Design Of Hybrid Hofsmentioning
confidence: 99%
“…In hydrogen‐bonded sulfonate frameworks, with guanidinium, [19] hexaaqua, [20] or hexaammine metal cations, [21] the flexibility of the charge‐assisted hydrogen‐bonding with larger cations enables the inclusion of a diverse range of guests. Unfortunately, both classes of material often lack structural stability upon removal of guest compounds, although some exceptions have been reported [21,22] …”
Section: Introductionmentioning
confidence: 99%